If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 6) + -5 = -47 Reorder the terms: -7(6 + x) + -5 = -47 (6 * -7 + x * -7) + -5 = -47 (-42 + -7x) + -5 = -47 Reorder the terms: -42 + -5 + -7x = -47 Combine like terms: -42 + -5 = -47 -47 + -7x = -47 Add '47' to each side of the equation. -47 + 47 + -7x = -47 + 47 Combine like terms: -47 + 47 = 0 0 + -7x = -47 + 47 -7x = -47 + 47 Combine like terms: -47 + 47 = 0 -7x = 0 Solving -7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-7'. x = 0 Simplifying x = 0
| 12-n=1.4 | | x^2-33*x+252=0 | | 3(w-6)=8w+2 | | b=x-my | | 5x+3=-67 | | 5(4y-8)-(4y+4)= | | 9x-2+2(x+3)=180 | | 1+x=-5+25 | | 5(3+5x)-2=8 | | 8-x=-2x-1 | | 21=5x+3x+4 | | 9y+7=14y+7 | | 81-4(9-3)= | | y-(250-75)=15 | | 32x(4x)=72 | | 2(x-4)+12(x-3)=180 | | |2x-3|=-7 | | 3.5x-2.1x=6.1 | | 10-4x=3x-4 | | y-1=m(x-(-2)) | | 3x-8+9x+2=90 | | -2x+y=15 | | 3.5x-2.11x=6.1 | | 4+5x=3+3x | | 5x^4-1=0 | | -8y+3(y+6)=38 | | 1.07(4x+10+5.30)=1.08(4x+5+8.60) | | 4+2x+3x=3x+3 | | 15y+31=31 | | 4+2x+3x=2x | | 7(5x+2)+9=58 | | 13+17=-5(4x-6) |